2000
DOI: 10.1034/j.1600-0765.2000.035005310.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of macromolecular clearance via lymph flow in hamster gingiva by topical warming and massage

Abstract: The lymphatic system is very important for macromolecular clearance in various tissues, especially in the gingiva. However, the kinetics of macromolecular clearance via the lymph flow in the gingiva are poorly understood. The aim of this study was to investigate whether thermal or mechanical stimulation affects macromolecular clearance via the lymph flow in the gingiva. Carbon black suspension was injected into the mandibular gingiva of anesthetized hamsters and its drainage into cervical lymph nodes was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
1
11
1
1
Order By: Relevance
“…We have found that both methods can be applied on the human gingiva with distinct benefits. Warmed saline is routinely applied in the oral cavity as a daily rinse after tooth extraction to prevent alveolar osteitis (43) and it may improve oedema as well by stimulating lymphatic circulation (52). Based on our experiments, local warming can have additional benefits after oral flap surgery as it may increase blood flow in the low perfused flap, especially after augmentation procedures.…”
Section: Discussionmentioning
confidence: 94%
“…We have found that both methods can be applied on the human gingiva with distinct benefits. Warmed saline is routinely applied in the oral cavity as a daily rinse after tooth extraction to prevent alveolar osteitis (43) and it may improve oedema as well by stimulating lymphatic circulation (52). Based on our experiments, local warming can have additional benefits after oral flap surgery as it may increase blood flow in the low perfused flap, especially after augmentation procedures.…”
Section: Discussionmentioning
confidence: 94%
“…Warming of gingiva. Thermal treatment of the gingiva was conducted as previously described [5]. Briefly, we warmed the mandibular gingiva of hamsters at 408C for 2 minutes with the special device illustrated schematically in Figure 1.…”
Section: Animalsmentioning
confidence: 99%
“…The gingiva is one of the tissues susceptible to inflammatory edema caused by increased vascular permeability [4]. Recently we reported that topical warming significantly stimulated macromolecular clearance via lymph flow in the gingiva [5] and decreased the swelling of the gingiva.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, we intend to study various growth factors of lymphatic vessels in newly formed regions to distinguish them from blood vessels. We previously reported a time-course study of macromolecular clearance by lymph vessels in the tongue (Xie and Fujimura, 2000), and hyperthermia stimulated lymphatic absorptivity in ginigva (Shimotoyodome et al, 2000) using RI labeling albumin, and we hypothesize that these phenomena are caused by the same effect, hyperthermia. We have already examined the lymphatic architecture of the tongue using enzymehistochemical staining (Liang and Fujimura, 2000) and our method (Fujimura, 1999), and have examined the relationship between the morphology and function of lymph vessels.…”
Section: Discussionmentioning
confidence: 89%